Model-driven software engineering methodology in the framework approach - Dyshlyk, O.; Chabaniuk, V. (Land Management, Cadastre and Land Monitoring, 2026)
The research of the “Framework Approach to Handling with (Hierarchical) Spatial Information Systems (SpIS)”, hereinafter referred to as the Framework Approach, was continued. Prior to this, the entities of the Framework Approach, which relate to the upper echelons of its epistemological hierarchy, were considered. Namely, to (the title of the article corresponding echelon is given in quotes “…”): 1) the first echelon – “Framework Approach as a Strategy for Research and Design of Complex SpIS (on the Example of NGDI)”; 2) again the first echelon – “Microsoft Solutions Framework (MSF) as a Generalized Methodology of the Framework Approach for Handling SpIS”; 3) the second echelon – “Standardization of the MSF Agile Methodology using ISO/IEC 24744 standard”; 4) the third echelon – “On the Methodics of the Framework Approach to Creating SpIS Using Modern Microsoft Technologies”. Echelons unite groups of users of a modeling system. They correspond to strata of the same system. Three of the four mentioned articles use significantly the special knowledge about MSF and about modern information technologies (IT) of Microsoft. To reduce dependence on this knowledge, in this article we used “neutral” knowledge about software development methodologies. For this purpose, the so-called Model-Based Software Engineering (MBSE) is considered through the “framework prism”. The latter is Model-Based System Engineering (MBSysE) and, more generally, Model-Based Engineering (MBE). Their understanding is necessary to create our own methodology, which is called the Pattern-Based Spatial Engineering (PBSpE) methodology. PBSpE will include the methodics of extending the SpIS, which were mentioned in our works earlier. Moreover, these methodics have already been used by us in practice, sometimes without association with any methodology. It should be noted that our SpIS extension methodics are applied to constructions that are already structured as a result of using the so-called Atlas Solution Framework AtlasSF. Received: 09.12.2025; Accepted: 25.03.2026;